Supersymmetric AdS 6 black holes from matter coupled F(4) gauged supergravity - Minwoo Suh (Journal of High Energy Physics, 2019)
Abstract In matter coupled F(4) gauged supergravity in six dimensions, we study supersymmetric AdS 6 black holes with various horizon geometries. We find new Ad S 2 × Σ g 1 × Σ g 2 $$ AdS_2× {\varSigma}_{{\mathfrak{g}}_1}× {\varSigma}_{{\mathfrak{g}}_2} $$ horizons with g $$ \mathfrak{g} $$ 1 > 1 and g $$ \mathfrak{g} $$ 2 > 1, and present the black hole solution numerically. The full black hole is an interpolating geometry between the asymptotically AdS 6 boundary and the Ad S 2 × Σ g 1 × Σ g 2 $$ AdS_2× {\varSigma}_{{\mathfrak{g}}_1}× {\varSigma}_{{\mathfrak{g}}_2} $$ horizon. We also find black holes with horizons of Kähler four-cycles in Calabi-Yau fourfolds and Cayley four-cycles in Spin(7) manifolds.